Efecto de seis tratamientos bajo tres condiciones de fertilización en las diferentes variables agronómicas del cultivo de raphanus sativus (rábano), 2021 - Villanueva Montoya, Luzbeth Lindsay (2022)
For this investigation, the following problem was proposed: is there the same effect _x000D_ between the six treatments under three fertilization conditions for each agronomic variable _x000D_ of the radish crop? The general objective of this work is to determine the mean effect of _x000D_ radish plants with six different treatments, under different fertilization conditions. The _x000D_ simulation of the data had as reference the thesis of Gómez, L. (2011)._x000D_ The main problem of radish cultivation is due to the poor assimilation of nutrients and _x000D_ having a very short life cycle (35 days), chemical fertilizers take time to dissolve, therefore _x000D_ the plant does not absorb the nutrients necessary for its growth and development, that is why _x000D_ in this research a nested design was carried out with two factors F1: Fertilization condition, _x000D_ F2: treatments, applied to each of the radish plants, which were divided under three _x000D_ fertilization conditions and five repetitions per treatment. In order to identify and compare, _x000D_ which of the factors will have the greatest average effect between the different agronomic _x000D_ variables?_x000D_ It was concluded that the best average effect was obtained by the organic fertilization _x000D_ condition in the two treatments applied to each radish plant: Goat-sheep vermicompost and _x000D_ Bovine vermicompost with liquid earthworm humus